Maternal and congenital cytomegalovirus infections in a population‐based pregnancy cohort study. Issue 12 (30th October 2018) - Barlinn, Regine; Dudman, Susanne G.; Trogstad, Lill; Gibory, Moustafa; Muller, Fredrik; Magnus, Per; Rollag, Halvor
Abstract : CMV is the most common cause of congenital infection. During the past few decades, there has been a change in behaviour that possibly has affected the CMV infection rate of mother and child. We investigated 1350 randomly selected pregnant women from the Norwegian Mother and Child Cohort Study using an algorithm for detection of maternal and congenital CMV (cCMV) infection including both serology and nucleic acid amplification assay. The CMV IgG seroprevalence was 54% and 23 (3.7%) mothers seroconverted. Three (0.22%) children had a positive CMV PCR in the umbilical cord blood. The transmission rate was lower than reported in previous studies, probably due to lower sensitivity in plasma compared to saliva and urine. The prevalence of cCMV in the present study was compared with the number registered with the ICD‐10 code P.35.1‐congenital CMV infection in the Norwegian Patient Register. The number registered was lower than the number of estimated infections. Factors like lower level of education and parity were associated with higher CMV IgG seroprevalence, but no significant difference could be linked to age. In conclusion, in this cohort of pregnant women, a high CMV IgG seroconversion rate was found, while the vertical transmission rate was low.